Sruktur dan Fungsi Sosial Cerita Rakyat Legenda Talempong Batu di Kenagarian Talang Anau Kecamatan Gunuang Omeh Kabupaten Lima Puluh Kota - Sari, Ade Komala; Hasanuddin WS, Hasanuddin WS (Universitas Negeri Padang, 2024)
This study aims to describe: (1) the structure of the Talempong Batu legend folklore in Kenagarian talang Anau, Gunuang Omeh District, Lima Puluh Kota Regency, (2) the social function of the Talempong Batu legend folklore in Kenagarian Talang Anau, Gunuang Omeh District, Lima Puluh Kota Regency. This type of research is literary research in the field of oral literature using descriptive methods. The data of this research is the folklore of the legend of Talepong Batu in Kenagarian Talang Anau, Gunuang Omeh District, Lima Puluh Kota Regency. The collected data is then analyzed in several stages (1) data description stage (2) data classification stage or data analysis stage (3) discussion or conclusion stage of the classification or data analysis results (4) reporting stage. The results of this study are (1) the structure of the Talempong Batu legend folklore in Kenagarian Talang Anau Kecamtan Gunuang Omeh Kabupaten Lima Puluh Kota consists of; (a) the language style in the folk tale of the Talempong Batu legend uses the Minangkabau language in Kenagarian Talang Anau, Gunuang Omeh District, Lima Puluh Kota Regency, (b) characters and characterizations in the folk tale of the Talempong Batu legend there are two characters, Samsudin and Mother, (c) the setting in the story includes place setting, time setting, and social setting, (d) the plot or story is a conventional plot using three stages, namely, the initial stage, the middle stage, and the final stage, (e) theme (f) mandate.